Effects of a physical education program on physical activity, fitness, and health in children: The JuvenTUM project - Siegrist, M.; Lammel, C.; Haller, Bernhard; Christle, Jeffrey; Halle, M. (Scandinavian journal of medicine & science in sports, 2013)
The purpose of the study was to investigate the effects of a school-based prevention program on physical activity, fitness, and obesity. We performed a prospective study in eight Bavarian primary schools (n=724 children, 8.4±0.7years) randomized one to one to either an intervention school (IS, n=427) or a control school (CS, n=297). Children in IS attended 10 health-related lessons at school over a period of 1year. Parents and teachers attended two and three educational health-related lessons, respectively, and also received 10 newsletters on health issues. Daily physical activity (≥60min/day), physical fitness (six-item test battery), and anthropometric data were obtained at baseline and after 1year. Physical activity and physical fitness increased in IS, but it failed to reach significant intervention effects. Nevertheless, a reduction in waist circumference was observed for all children [mean change 1.7cm; 95% confidence interval (CI) 1.2-2.3; P<0.001). This effect was more pronounced in overweight children (>90th percentile, n=99, mean change 3.2cm; 95% CI 1.5-4.8; P<0.001). This easily administered preventative program involving children, parents, and teachers revealed that a generalized approach increasing physical activity will even be favorable in a subgroup of obese children. © 2011 John Wiley & Sons A/S.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Exercise; Health education; Motor fitness; School program; Waist circumference; Youth